LRFD Crane Girder Design Procedure and Aids - Laman, Jeffrey A. (Engineering Journal, 1996)
The design of crane girders and supporting columns has traditionally followed allowable stress design (ASD) philosophy. With the growing acceptance of load and resistance factor design (LRFD) it has become important to review the ASD design procedures and to establish the corresponding design procedures in an LRFD format. In addition, new design charts and tables will make the design of these industrial building elements much simpler and less time consuming. This paper discusses the steps for LRFD design procedures, reviews the critical limit states, and presents design tables and charts useful for wide flange and channel combination sections.